The Meaning of Psychological Security for Students in the Implementation of Child-Friendly Islamic Boarding Schools - Sabiq, Zamzami (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the meaning of psychological safety for santri in the context of the implementation of the Pesantren Sharing and Care (PSP) program carried out by the Ministry of Religious Affairs of Sumenep Regency. The background of this study is the increasing awareness of the importance of creating a pesantren environment that is not only religious but also child-friendly and supportive of the psychosocial well-being of santri. Using a qualitative approach with a case study method, data was collected through in-depth interviews, field observations, and documentary studies at two boarding schools targeted by the PSP program. Data analysis was conducted using thematic analysis. The research findings revealed four main themes related to psychological safety: (1) feeling safe to speak up and express opinions without fear of punishment, (2) the development of empathetic relationships between students and caregivers, (3) the importance of physical spaces that support emotional comfort, such as counseling rooms and gardens, and (4) challenges posed by seniority culture and hidden violence that still persist. The PSP program plays a significant role in creating a more open, participatory, and caring environment that addresses the emotional needs of students. However, achieving a comprehensive transformation of values requires time, continuous evaluation, and structural and cultural support from all elements of the boarding school.